Anger Proneness and Prognostic Pessimism in Men With Prostate Cancer. (July 2017) - Gerhart, James; Schmidt, Eric; Lillis, Teresa; O'Mahony, Sean; Duberstein, Paul; Hoerger, Michael
Aim: Anger is a common reaction to cancer diagnosis which may impact patients' perceptions of their prognosis and goals of care. This study tested the hypothesis that men with prostate cancer who are anger prone are pessimistic regarding their cancer prognosis. Methods: Two hundred and twelve men with a history of prostate cancer completed measures of personality traits, their prostate cancer prognosis, and their perception of their doctor's assessment of their prognosis. Anger proneness was operationally defined by the presence of high levels (ie, above the medians) of neuroticism and disagreeableness. Results: One in 4 men with prostate cancer disagreed with their doctor about prognosis. Anger-prone participants endorsed more pessimistic perceptions of prognosis ( P = .041). This significant association was maintained after accounting for potential confounders. Conclusion: Greater attention paid to patient anger regulation style and pessimistic perceptions will improve discussions about prognosis and goals of care among men with prostate cancer. Given recent calls for wider distress screening and earlier palliative care intervention in cancer settings, providers have an unprecedented opportunity to assess and respond to anger in the clinical setting. Communication could be improved through empathic statements that convey realistic optimism when appropriate, a commitment to the patient–provider relationship and a willingness to explore and address patient needs.